Implementation of Building Information Modeling (BIM) Using Hybrid Z-DEMATEL-ISM Approach - Ali RezaHoseini; Elmira Ahmadi; Pantea Saremi; Morteza BagherPour (Advances in Civil Engineering)
Due to the shortcomings of the traditional construction project management system, there is a feeling among those involved in this industry that new tools and approaches should be used to facilitate simple and complex operations. On the contrary, there is no integrated database for all construction sectors, and of course the relationship between these sectors is a major problem for any construction project. The technology and tool that overcomes many of these shortcomings is BIM technology. This paper seeks to identify all the challenges that hinder the successful implementation of BIM and determine important challenges based on Z-DEMATEL-ISM Hybrid approaches. The DEMATEL method is used to obtain the weight of the challenges and the most influencing and influenced challenges. The ISM approach is then employed to design a hierarchical network of challenges and tries to determine the level and impact of each challenge in the planned structure. For closeness to the real-world, Z-number (an ordered pair of fuzzy numbers, where the first component controls on a fuzzy variable, and the second component is a measure of reliability for the fuzzy component) is also used to consider the expert’s mental uncertainties in the final results. This research tries to examine the literature related to the subject and consider the sources and opinions of many professors and university experts based on the filled questionnaires. The findings of this paper show that “misunderstanding the BIM technology” is recognized as the most important challenge with the most weight. At the same time, “lack of governmental support” is the most influencing challenge, and “lack of interaction and teamwork” is the influenced challenge.